Cyberbullying en escolares de educación secundaria de Lima Metropolitana - García Ampudia, Lupe (2010)
Violence among coetaneans acquires new expressions due to the impact of new technologies of information and communication (TICs) in this current generation, these new expressions identify cyberbullying as an intimidating practice used by adolescents with their coetaneans. The objective of this research is to know the prevalence of cyberbullying, establish the differences in genre, school grade and aut.perceived academic performance from the position of the aggressive person or victim, and also the ways which are most used by schoolchildren to intimidate their coetaneans, The sample consisted of 1,703 students from 3rd to 5th high school in public schools in Lima, to collect data, we used the “Cyberbullying questionnaire” (Ortega, Calmaestra y Mora Merchán, 2007) which was adapted by the research team; The results show that the prevalence of cyberbullying is more frequent using the internet than using mobile phones, from the perspective of genre, women are more victimized than men, there are meaningful differences from the position of the aggressive person and victim, this related to the auto-perceived academic performance but not related to the school grade or level; in the different ways of cyberbullying on the internet and on mobile phones, women are more victimized than men, students with regular auto-perceived academic performance are more intimidated and concerning to the school grade, there are differences only in students of 4th and 5th grade in some forms using mobile phones and the internet.